2021
DOI: 10.1038/s41434-021-00246-w
|View full text |Cite
|
Sign up to set email alerts
|

Current status and perspective of CAR-T and CAR-NK cell therapy trials in Germany

Abstract: Chimeric antigen receptor (CAR)-T cell therapies are on the verge of becoming powerful immunotherapeutic tools for combating hematological diseases confronted with pressing medical needs. Lately, CAR-NK cell therapies have also come into focus as novel therapeutic options to address hurdles related to CAR-T cell therapies, such as therapy-induced side effects. Currently, more than 500 CAR-T and 17 CAR-NK cell trials are being conducted worldwide including the four CAR-T cell products Kymriah, Yescarta, Tecartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
120
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(131 citation statements)
references
References 76 publications
0
120
0
Order By: Relevance
“…Remarkably, preclinical testing of HER-2-specific NK-92 cells (NK-92/5.28.z) in an orthotopic xenograft mouse model of glioblastoma demonstrated a dramatic increase in survival (200.5 days) compared to mice treated with control NK-92 cells (73 days) (139). Intracranial injection of NK-92/5.28.z cells are being evaluated in the ongoing CAR2BRAIN clinical trial for recurrent glioblastoma, with no toxicities reported thus far at three dose levels (NCT03383978) (140,141). Although the field of CAR-NK cell therapy is still relatively new, preliminary results have been promising, and the first ever clinical trial of CAR-NK cells for glioblastoma will indeed shed light on whether this immunotherapy can bring benefit to patients.…”
Section: Car Immunotherapiesmentioning
confidence: 99%
“…Remarkably, preclinical testing of HER-2-specific NK-92 cells (NK-92/5.28.z) in an orthotopic xenograft mouse model of glioblastoma demonstrated a dramatic increase in survival (200.5 days) compared to mice treated with control NK-92 cells (73 days) (139). Intracranial injection of NK-92/5.28.z cells are being evaluated in the ongoing CAR2BRAIN clinical trial for recurrent glioblastoma, with no toxicities reported thus far at three dose levels (NCT03383978) (140,141). Although the field of CAR-NK cell therapy is still relatively new, preliminary results have been promising, and the first ever clinical trial of CAR-NK cells for glioblastoma will indeed shed light on whether this immunotherapy can bring benefit to patients.…”
Section: Car Immunotherapiesmentioning
confidence: 99%
“…Therapeutic cell engineering killer (NK) cells engineered with CAR (CAR-NK) show fewer adverse effects than T cell therapy, and are more amenable to off-the-shelf manufacturing (Albinger et al, 2021;Schmidt et al, 2021). Although CAR receptors are only functional in immune cells, cell-to-cell contact can also be modulated in other cell types (Fig.…”
Section: Closed-loop-mediated Therapeutic Genetic Circuitsmentioning
confidence: 99%
“…The success of CAR T-cells therapy in cancer is exemplified by numerous clinical trials that have shown that 70–90% complete remission (CR) can be achieved in pediatric and adult patients treated with CD19-directed CAR T-cells ( Xu et al, 2019 ). Based on these growing CAR-T cell immunotherapy achievements, over 500 clinical trials worldwide analyzing CAR-T cells for the treatment of cancer are currently being under evaluation, and the majority are being performed in East Asia (269 trials), followed by the US (225 trials), and Europe (62 ongoing studies) (as registered at clinicaltrials.gov Q3 2020) ( Albinger et al, 2021 ). So far, five CAR-T cell therapy agents were approved by FDA for cancer treatment: Tisagenlecleucel (Kyrmriah®) for treatment of acute lymphoblastic leukemia (ALL) ( Mullard 2017 ), Axicabtagene ciloleucel (Yescarta™) for diffuse large B-cell lymphoma (DLBCL) and also FDA-approval for follicular lymphoma in april 2021 ( Bouchkouj et al, 2019 ), Brexucabtagene autoleucel (Tecartus™) for treatment of mantle cell lymphoma (MCL) ( Al-Juhaishi and Ahmed, 2021 ), Idecabtagene vicleucel (ABECMA®) for treatment of multiple myeloma ( Munshi et al, 2021 ) and Lisocabtagene maraleucel (Breyanzi®) for diffuse large B-cell lymphoma treatment ( Iragavarapu and Hildebrandt 2021 ) ( Table 2 ).…”
Section: Immunotherapy a New Approach For Cancer Treatmentmentioning
confidence: 99%